Survival of patients with ruptured gastrointestinal stromal tumour treated with adjuvant imatinib in a randomised trial - Joensuu, Heikki; Reichardt, Annette; Eriksson, Mikael; Hohenberger, Peter; Boye, Kjetil; Cameron, Silke; Lindner, Lars H.; Jost, Philipp J.; Bauer, Sebastian; Schütte, Jochen; Lindskog, Stefan; Kallio, Raija; et al. (Springer Nature, 2025)
Background: Patients with ruptured gastrointestinal stromal tumour (GIST) have poor prognosis. Little information is available about how adjuvant imatinib influences survival.
Methods: We explored recurrence-free survival (RFS) and overall survival (OS) of patients with ruptured GIST who participated in a randomised trial (SSG XVIII/AIO), where 400 patients with high-risk GIST were allocated to adjuvant imatinib for either 1 year or 3 years after surgery. Of the 358 patients with confirmed localised GIST, 73 (20%) had rupture reported. The ruptures were classified retrospectively using the Oslo criteria.
Results: Most ruptures were major, four reported ruptures were reclassified unruptured. The 69 patients with rupture had inferior RFS and OS compared with 289 patients with unruptured GIST (10-year RFS 21% vs. 55%, OS 59% vs. 78%, respectively). Three-year adjuvant imatinib did not significantly improve RFS or OS of the patients with rupture compared with 1-year treatment, but in the largest mutational subset with KIT exon 11 deletion/indel mutation OS was higher in the 3-year group than in the 1-year group (10-year OS 94% vs. 54%).
Conclusions: About one-fifth of ruptured GISTs treated with adjuvant imatinib did not recur during the first decade of follow-up. Relatively high OS rates were achieved despite rupture.